An investigation on asset allocation and performance measurement for unit trust funds in Malaysia using multifactor model: a post crisis period analysis - Ali Ahmed, H.; Lee, T.; Shaikh, Junaid (Inderscience Enterprise Ltd, UK, 2011)
This study examines the pattern of asset allocation and the performance of unit trust in Malaysia over the post crisis period by using risk-adjusted performance measures and multi-factor model from the year 2000 to 2004. Evidence from the statistics suggests that an active asset allocation strategy had been observed among Malaysian fund managers during the post Asian financial crisis. It is also suggested that investment allocation in equity remained a dominant vehicle for investment and asset allocation. Findings from multifactor model suggest that all funds of different objectives registered positive alphas except for income funds, with growth funds being among the top. While balanced funds registered highest diversification effectively, diversifying away about 70%–80% of unsystematic risk, the momentum factor is not among the important elements to explain unit trust performance in Malaysia. © 2011 Inderscience Enterprises Ltd.